The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2003
DOI: 10.1143/jjap.42.l804
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Aligned Carbon Nanofibers at 200°C

Abstract: This paper provides an overview of two topics. First, it presents a unified approach to various techniques addressing the non-uniqueness of the solution of the inverse gravimetric problem; alternative, simple proofs of some known results are also given. Second, it summarizes in a concise and self-contained way a particular multiscale regularization technique involving scaling functions and wavelets. 0266-5611/08/045019+25$30.00

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 4 publications
0
13
0
Order By: Relevance
“…Although such hot spots were not identified by thermography, local plasma heating is highly anticipated which eventually promotes reaction between adsorbed CO 2 and neighboring carbonaceous species. Another possibility is the chemical etching by active hydrogen [61]. This phenomena is well investigated in carbon nanotube growth [62,63].…”
Section: Comparison With Thermal Reactionmentioning
confidence: 99%
“…Although such hot spots were not identified by thermography, local plasma heating is highly anticipated which eventually promotes reaction between adsorbed CO 2 and neighboring carbonaceous species. Another possibility is the chemical etching by active hydrogen [61]. This phenomena is well investigated in carbon nanotube growth [62,63].…”
Section: Comparison With Thermal Reactionmentioning
confidence: 99%
“…Thus, PECVD allows nanotubes to been grown at lower temperatures. [11][12][13][14][15][16][17][18][19][20] For example, Hofmann et al 12 13 observed that the low-power plasma-enhanced chemical vapor deposition (PECVD) of MWNTs using Ni, Co or Fe as a catalyst and acetylene/ ammonia mixture as growth gas gave a growth activation energy of order 0.23 eV (Fig. 2), which is much lower than that found by simple thermal CVD.…”
Section: Low Temperature Growthmentioning
confidence: 99%
“…This paper was presented at the AVS 51st International Symposium held in Anaheim CA, November [14][15][16][17][18][19]2004. NSC-92-2622-E-007-016.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…5 In the catalytic CVD processes, a gas mixture containing hydrocarbon precursors serving as carbon sources for CNT growth such as methane ͑CH 4 ͒ or acetylene ͑C 2 H 2 ͒ and a second gas such as hydrogen ͑H 2 ͒ or ammonia ͑NH 3 ͒ for maintaining catalysts active by etching away amorphous carbon ͑a-C͒ deposits are often employed. [16][17][18] The measurements of these plasma properties can also enhance our understanding of the basic physical and chemical mechanisms associated with catalytic synthesis of CNTs. 13 For plasmaenhanced processes, the relative concentration of different chemical species is also strongly correlated with electron temperature, in addition to the plasma density.…”
Section: Introductionmentioning
confidence: 99%